Esquisse d’une approche intersectionnelle de la loi du 15 mars 2004 sur le port de signes ou de tenues manifestant une appartenance religieuse dans les écoles, collèges et lycées publics - Marc Thérage (Criminocorpus)
The law of 15 March 2004 on the wearing of signs or outfits demonstrating a religious affiliation in public primary and secondary schools is presented by the legislator as a simple application of the principle of secularism. The title of the law only mentions the principle of secularism while parliamentarians insist during debates on gender equality, affirming that this text has the main target – if not the only one – of prohibiting wearing a headscarf in public primary and secondary schools. Since 2004, gender and the supposed religion of racialised women thus appear curiously linked. Drawing on the intersectional approach of Kimberley Crenshaw, enlarged by postcolonial studies, this critique of the 2004 law – presented as « against Muslim headscarves » – and of the discourses surrounding it, makes it possible to underline the existence of a legal discrimination against women of color who live a specific discriminatory experience based on gender, skin colour and/or real or supposed religion, an imaginary split within nationals by distinguishing those who have parents or grandparents who immigrated to France from former colonised territories, age, social condition and/or place of residence as evidence of original social background … The apparent neutrality of the text of the 2004 law conceals a combination of discriminatory factors. This text, both racist and antifeminist, consecrates a white and male subjectivity, yet presented as non-racial, non-gendered and objective.